Genomic Databases and Biobanks in Denmark. Issue 4 (2015) - Hartlev, Mette
Abstract : Denmark is a constitutional monarchy resting on the founding Constitution of 1849 and later amendments. The 179 members of parliament are democratically elected, and the government is formed on the basis of parliamentary principles. The queen functions as head of state without any power to intervene in legislative or executive matters. Greenland and the Faroe Islands are part of the kingdom, but self-governing. In total, the population is around 5.6 million. The country is divided into five regions and 98 municipalities. Members of both regional and municipal councils are democratically elected.